Language Economy and its Implications for Language Teaching: Data and Evidence - Balazs Huszka; Yuki Akita; Min Shen; Nor’Azmah Yunus (LingPoet: Journal of Linguistics and Literary Research, 2021)
In the following paper we are going to elaborate on a lately less-researched topic, the language economy, the ever-evolving nature of languages and their pursuit for simplicity. Our analysis conceptualizes how language economy leads to seemingly “ungrammatical” forms that are still widely accepted and used by native speakers, and we discuss the possibility of their inclusion into foreign language teaching. Our data are from the German language; however, in our reasoning for a less “perfect-grammar” centered way of teaching, we are going to use Japanese and Chinese examples as well.